El comportamiento organizacional como estrategia de mejora del desempeño laboral en las organizaciones. Caso de estudio Empresa Pública de Movilidad de la Mancomunidad de Cotopaxi. - Acurio Espinosa, Diego Wilfrido (2022)
This project had the objective of establishing how the organizational behavior of the EPMC influences the work performance of its collaborators, to generate strategies that improve the work environment in which they operate, through the identification of the type of organizational behavior models that exist. for the adaptation or location of potentialities, the diagnosis of the organizational behavior of the EPMC and the definition of strategies to optimize work performance, correcting problems and taking advantage of existing opportunities. The quantitative methodology of the exploratory descriptive type was used, the surveys of the nine managers and 54 employees of the organization. It was evidenced that there is not enough autonomy, the work is monotonous, there is a low perception in the practice of values, teamwork does not prevail, there are attitudes that are aligned with the style of democratic leadership, which negatively affects the worker performance. For this, an Organizational Behavior Model was proposed as an alternative solution to strengthen organizational values, transformational leadership, assertive communication, teamwork and conflict resolution.